A Mechanistic Approach to enhance the efficiency of endoxifen by conjugating with anticancer tripeptides: In-Silico and molecular dynamics studies. - Anamika Jain,; Swati Sahu,; Richa Tripathia,; Ekta Verma,; Shaheen Begumb,; Shailendra Patil,; Asmita Gajbhiye, (The Bioscan, 2025)
Background: Globally, women are concerned about their health due to breast cancer. Researchers are focusing on enhancing the quality of life for breast cancer patients, as of right now, there isn't a single treatment that can be used to cure breast cancer permanently. Aims: This research aims to enhance the effectiveness of tamoxifen derivative through conjugation with anticancer tripeptides, as ascertained through molecular docking studies. Methods: We conducted an in-silico study with NGR and RGD tripeptides conjugated with tamoxifen derivatives using the AutoDock tool. Results: The following significant binding energy interaction was observed with protein 3ERT like Endoxifen -7.2 kcal/mol; Tamoxifen-7.8 kcal/mol; 4-Hydroxy tamoxifen -7.9 kcal/mol; N- desmethyl tamoxifen -7.9 kcal/mol; NGR tripeptide -6.8 kcal/mol; RGD tripeptide -5.4 kcal/mol; P1-9.8 kcal/mol; P2-10.0 kcal/mol; P3 -11.0 kcal/mol; P4 - 10.9 kcal/mol; P5 -8.5 kcal/mol. Furthermore, the interaction and stability behavior of the RGD tripeptide conjugated with endoxifen and NGR tripeptide complexes were analyzed for a 100-nanosecond (ns) time. Calculated RMSD values observed using molecular dynamics simulation (MDS) were found to be -0.3 nm respectively. RMSF calculation per residues showed a value near 0.2nm to -0.4nm and -0.2nm to -0.3nm respectively. Rg values remained between -1.9 nm to -1.95 nm. SASA analysis reveal the solvent behaviour of the complexes. The total number of hydrogen bonds was monitored during the simulation time and the results showed that around two hydrogen bonds were established with the active site for the RGD tripeptides conjugated with endoxifen. The hydrogen bonds were observed with LEU 536 and VAL534 residues and for NGR tripeptide conjugated with n-des methyl tamoxifen hydrogen bond observed with LEU 536 residues in the molecular docking. Conclusion: Thus, significant docking interaction and stable dynamicity of endoxifen conjugated with tripeptides had the best docking and dynamic results. The next phase involves synthesizing these tripeptides and conjugating them with endoxifen for in-vitro cell line investigations.